Isolation and initial characterization of a uracil auxotroph of the blue-green alga Anacystis nidulans. - Stevens, C L (1975)
A uracil-requiring auxotroph of Anacystis nidulans was isolated after treatment with N-methyl-N'-nitrosoguanidine. Neither precursors in the de novo pyrimidine pathway nor compounds of "salvage" or degradative pathways could replace the uracil requirement. The reversion frequency for mutation to a nonuracil requirement for growth was 2.0 times 10(-8). The calculated average rate of uracil utilization was 1.1 times 10(-17) mol of uracil per unit cell mass/h. The amount of uracil required for the synthesis of a unit cell mass was 3.8 times 10(-17) mol of uracil.